Critical Reading Skills Analysis Among Seventh-Grade Students at SMP Negeri 5 Padangsidimpuan - Harianja, Rizki Wulandari; Tambunan, Elissa Evawani; Ramadhani, Yulia Rizki; Tambunan, Mahrani (Yayasan Kajian Riset dan Pengembangan RADISI, 2025)
This study examines the critical reading skills of seventh-grade students at SMP N 5 Padangsidimpuan. Using a quantitative descriptive approach, the research assessed 30 students through a critical reading test based on Nurhadi's six aspects of critical reading: remembering explicit facts, interpreting implied meanings, applying concepts, analyzing content, synthesizing content, and evaluating reading material. Results indicate that students demonstrate very good abilities in five aspects, with scores ranging from 80 to 100, particularly excelling in remembering explicit facts (scores of 97-100) and evaluating content (scores of 90-97). However, synthesizing reading content emerged as an area needing improvement, with scores of 70 and 57. The overall average score of 85 places students' critical reading abilities in the